Research Trends and Exploration of The Impact International Certification on Industry Performance: A Bibliometric Analysis - Putra Irwandi; Feryanto Feryanto; Anna Fariyanti (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The development of the industry, which is increasingly oriented towards increasing competitiveness and quality, is closely related to the ownership of international certification in global competition. Industries that have international certification have a good reputation for improving industrial performance from financial and operational aspects. Purpose: This study aims to analyze research trends, conceptual networks of international certification, and their impact on industrial performance. Design/Methodology/Approach : The approach used in this study is exploratory with the help of bibliometric analysis visualization using r-packages and VOSViewer software. By using various exclusion and inclusion criteria, it was found that there were 450 relevant articles from the Scopus database in the 2014-2024 range with scientific fields, namely management, economics, business, and finance. Findings/Results: The results of the analysis show that there are positive and negative relationships due to the application of international certification. In general, the application of international certification has a positive impact in increasing consumer confidence, increasing the efficiency of company operations, broader market access, improving the image and reputation of the company in the international market. On the other hand, international certification does not always have a positive impact. In some cases, certification has resulted in high costs such as audit costs, training costs, testing, and periodic maintenance costs. In addition, the negative impact of international certification will increase the company's administrative burden, orient the consumer focus on price rather than quality, and not always provide added value. Conclusion: Hopefully, this research leads to the conclusion that international certification research has prospects in the preparation of future stakeholder policies.Originality/State of art: This study fills a gap in the literature by introducing a comprehensive analysis of the effect of international certification on industry performance using bibliometric analysis. A comprehensive bibliometric study of this research trend is under-researched. Different from previous studies that only focus on one industry or certification type, this research conducts analyses across sectors and regions, offering a more in-depth global perspective. Bibliometric techniques such as co-citation and temporal analysis are increasingly being used to understand research patterns in the international certification literature Keywords: bibliometrics, conceptual networks, international certification, industrial performance, research trends